2021
DOI: 10.1111/iwj.13571
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a new dried human amnion derived membrane in addition to standard care in treating diabetic foot ulcers: A patient and assessor blind, randomised controlled pilot study

Abstract: Recent reviews suggest that amniotic membrane products may accelerate healing of diabetic foot ulcers. A new dried human amniotic membrane (dHAM) has been used for ocular ulcers but not for diabetic foot ulcers. This was a multi‐centre, prospective, patient and observer blind, randomised controlled pilot trial, to investigate whether 2 weekly addition of the dHAM to standard care versus standard care alone increased the proportion of healed participants' index foot ulcers within 12 weeks. Thirty‐one people (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…A multicenter, double‐blinded RCT demonstrated that human amniotic membrane preparation is safe and promising for DF treatment. 36 Amniotic membrane allografts could facilitate wound closure with standard therapy in chronic ulcers that are resistant to closure, 37 which indicates that amniotic membrane allografts are promising for improving wound healing. Various modalities such as human amniotic membrane preparations, growth factors, stem cells, cultured fibroblasts, keratinocytes were applied to treat difficult‐to‐heal ulcers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter, double‐blinded RCT demonstrated that human amniotic membrane preparation is safe and promising for DF treatment. 36 Amniotic membrane allografts could facilitate wound closure with standard therapy in chronic ulcers that are resistant to closure, 37 which indicates that amniotic membrane allografts are promising for improving wound healing. Various modalities such as human amniotic membrane preparations, growth factors, stem cells, cultured fibroblasts, keratinocytes were applied to treat difficult‐to‐heal ulcers.…”
Section: Resultsmentioning
confidence: 99%
“…Recent co‐cited references focused on foot ulcers, amniotic membrane, osteomyelitis, and diabetic wound healing. A multicenter, double‐blinded RCT demonstrated that human amniotic membrane preparation is safe and promising for DF treatment 36 . Amniotic membrane allografts could facilitate wound closure with standard therapy in chronic ulcers that are resistant to closure, 37 which indicates that amniotic membrane allografts are promising for improving wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 10 studies of placental-derived products, 163,216,[229][230][231][232][233][234][235][236] which between them included a total of 886 participants.…”
Section: Placental Derived Productsmentioning
confidence: 99%
“…Of these, one described the use of dehydrated amnion/ chorion graft, 234 six the use of dehydrated human amniotic membrane (dHAM), 163,229,231,232,235,236 with one the use of cryopreserved placental membrane, 230 one the use of dehydrated human umbilical cord, 233 and one powdered dehydrated amniotic membrane. 216 Outcome: complete wound healing.…”
Section: Placental Derived Productsmentioning
confidence: 99%
See 1 more Smart Citation